A nutrient analysis of traditional Anishinaabe recipes and the role of folic acid in the regulation of anti-diabetic GLP-1 - Roque, Connor Francis (Laurentian University of Sudbury, 2022)
Type 2 diabetes (T2D) is a metabolic disease that results from insulin resistance or limited insulin production. The prevalence of T2D disproportionally burdens Indigenous people in Canada. Interventions including dietary change can improve diabetes outcomes; however, many aspects of Indigenous food knowledge and their role in metabolic health have not been investigated. This research sought to examine traditional Anishinaabe recipes and the metabolic effects of abundant nutrients within them. Several beneficial nutrients were identified, including folate. As folate is known to have a valuable role in metabolic health, we explored the effect of folic acid on the regulation of the antidiabetic hormone glucagon-like peptide-1 (GLP-1) from endocrine cells. A 24-hour 1.0 mM folic acid treatment produced a 1.690 ± 0.12-fold increase in GLP-1 secretion in a GLUTag-cell line. This research demonstrates that traditional Indigenous foods may have beneficial metabolic effects, and traditional knowledge can inform basic science research. Master of Science (MSc) in Biology